THE PROBLEMS OF ENVIRONMENT AND GREEN ECONOMY - Alimova Saboxat Gaziyevna; Erkinova Sevinch (Western European Studies, 2025)
This article identifies the most pressing environmental and other risks, as well as recommends policy changes and actions. Some of the issues discussed include measures to improve energy efficiency and landscape restoration programs, which simultaneously benefit the economy and the environment while also posing potential negative impacts on human health
Keywords: environmental and economic problems; green economy; economic development